2019
DOI: 10.1016/j.joca.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular expression patterns in the synovium and their association with advanced symptomatic knee osteoarthritis

Abstract: s u m m a r yObjective: Osteoarthritis (OA) is a major source of knee pain. Mechanisms of OA knee pain are incompletely understood but include synovial pathology. We aimed to identify molecular expression patterns in the synovium associated with symptomatic knee OA. Design: Snap frozen synovia were from people undergoing total knee replacement (TKR) for advanced OA, or from post-mortem (PM) cases who had not sought help for knee pain. Associations with OA symptoms were determined using discovery and validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…We also detected expression of vascular endothelial growth factor (VEGF), a signal protein produced by cells to stimulate blood vessel formation. VEGF is involved in bone tissue remodeling and new bone formation and is downregulated in patients with osteoarthritis [25]. Several immunomodulatory cytokines essential for regenerative medicine were identified.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected expression of vascular endothelial growth factor (VEGF), a signal protein produced by cells to stimulate blood vessel formation. VEGF is involved in bone tissue remodeling and new bone formation and is downregulated in patients with osteoarthritis [25]. Several immunomodulatory cytokines essential for regenerative medicine were identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies also showed an inverse relation between IL1R1 expression and the amount of IL-1β in OA joints. Wyatt et al showed that IL1R1 was downregulated in OA synovium compared to non-arthritic controls [94]. Moreover, in retinal endothelial cells, IL1R1 expression was downregulated during activation by IL-1β [95].…”
Section: Discussionmentioning
confidence: 99%
“… 146 Although this observation might be surprising in view of broadly held views that osteoarthritis pain originates from inflammatory processes in the synovium or subchondral bone, emerging molecular data from human tissue also support the notion that cartilage is the principal source of NGF in the osteoarthritis joint. Using agnostic approaches, NGF was not regulated in the synovium of individuals with painful compared with non-painful osteoarthritis, 27 , 79 and it was not found in bone marrow lesions from samples taken at the time of arthroplasty. 147 NGF was found to be regulated in damaged articular cartilage in early microarray studies of osteoarthritis cartilage, 148 and it defines one of seven subsets of chondrocytes identified by single-cell sequencing of human osteoarthritis cartilage.…”
Section: Targeting Nerve Growth Factor To Treat Osteoarthritis Painmentioning
confidence: 92%
“… 24 , 25 , 26 Additionally, various inflammatory molecules—including cytokines, chemokines, and metalloproteinases—have been measured in osteoarthritis cartilage and synovium. 27 , 28 …”
Section: Targeting Inflammation In Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation